(untitled) (Journal of Philosophy Culture and Political Science, 2019)
Abstract. 2016 marked the 25th anniversary of Uzbekistan’s independence. The article reviews the idea of independence and sovereignty and their link to energy. The author offers some questions to ponder about the balance between interdependence and independence, and the use every country can or should do with their natural resources. Uzbekistan is a hydrocarbons region producer. For this reason, the energy sovereignty connection is understood differently than in countries that are practically net recipients of energy or that are used as transit countries for oil and gas pipelines. The energy crisis of 1973 resulted in an economic crisis in 1974 and in subsequent years. Similarly, the economic crisis of 2008 caused a decrease in world energy consumption, which in turn led to producing countries entering the economic crisis. Experience shows that independence does not mean isolation but maintaining a balanced interdependence in relations with other countries. This article sets out tne argumebts inthiskey. Key words: Belt and Road Initiative, Central Asia, energy security, energy sovereignty, European Union, Uzbekistan.